2012
DOI: 10.1590/s0100-736x2012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores de risco de leptospirose bovina no Estado do Maranhão

Abstract: Foram investigados a prevalência e os fatores de risco da leptospirose bovina no Estado do Maranhão. O Estado foi dividido em quatro circuitos amostrais com base em parâmetros de produção distintos que variam conforme os diferentes sistemas de produção, as práticas de manejo, a finalidade de exploração, o tamanho médio dos rebanhos e os sistemas de comercialização. Objetivou-se estudar as características epidemiológicas da leptospirose bovina no Estado do Maranhão, de modo a determinar a prevalência em bovinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
1
14
1
10
Order By: Relevance
“…Those sera showing at least 50% of agglutination of leptospires in the microscopic field from the 1:100 dilution were considered positive (Galton et al, 1965;Cole et al, 1973;Silva et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Those sera showing at least 50% of agglutination of leptospires in the microscopic field from the 1:100 dilution were considered positive (Galton et al, 1965;Cole et al, 1973;Silva et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A amostragem foi delineada para a determinação da prevalência de propriedades positivas e de animais soropositivos, sendo selecionadas inicialmente as unidades primárias de amostragem (propriedades), e dentro delas, as unidades secundárias (animais), conforme metodologia descrita por Silva et al (2012).…”
Section: População De Estudounclassified
“…In this study, the animals were found to be negative for brucellosis, IBR and BVD indicating no circulation of these pathogens in the herd. Serological studies in cattle have shown that Leptospira infections are widespread in Brazil (FIGUEIREDO et al, 2009;HASHIMOTO et al, 2010;HASHIMOTO et al, 2012;HERRMANN et al, 2012;SILVA et al, 2012). Hardjo is considered to be the most common serovar in this animal species and has been reported as a major cause of infertility and abortions in seropositive herds (LILENBAUM; MARTINS, 2014).…”
Section: Resultsmentioning
confidence: 99%